Gestalt Counseling with Empty Chair Technique to Reduce Guilt among Adolescents at Risk: Array - Yessinta Wahyu Trijayanti; Juntika Nurihsan; Anne Hafina (Islamic Guidance and Counseling Journal, 2019)
Adolescent is defined as a period of transitional development from childhood to adulthood. This transition also requires adolescents to make some adjustment. Those who cannot adjust themselves to the transition may induce guilt in them. Guilt is an emotion that follows after a negative behavior. Gestalt counseling with empty chair technique can help counselees finish their "unfinished business", and one of the unfinished businesses is guilt. The research aims to test the effectiveness of Gestalt counseling with empty chair technique to reduce guilt among adolescents at risk. It adopted the quantitative approach with single subject research method. The sample was taken with a purposive sampling technique. The population included 16 adolescents at Yayasan Rumah Tumbuh Harapan in Bandung in 2018, with three adolescents with a high level of guilt as samples. Data were taken using Guilt Instrument. The research employed the A-B design. The results show a significant reduction of guilt based on the mean score in the baseline test and the mean score after the intervention. The mean baseline score of counselee ES was 67.01, and after the intervention, the score fell to 50.19; the mean baseline score of counselee FLO was 85.79 and went down to 76.72 after the intervention, and the mean baseline score of counselee PK was 77.64 and decreased to 63.91 after the intervention. Thus, it can be concluded that Gestalt counseling with empty chair technique is in general effective to reduce guilt.